The Society of Orthodox Parishes of Petrograd and its Province (1920–1922): the Experience of Sobornost under Persecution - Goltsov, Nikita V. (Вестник Свято-Филаретовского института)
This article is devoted to the history of the Society of Orthodox Parishes of Petrograd and its Province — a public organization registered by the Soviet government in 1920, which during its 18 months of existence united around 70 parishes of the Petrograd diocese. In 1922, it was administratively dissolved, and its board members found themselves at the centre of accusations of resisting the seizure of church valuables. In addition to the general issues that have been considered to a greater or lesser extent in historiography (the circumstances of the Society’s emergence, its purpose, structure, and main activities), in this article the author explores the founders’ ecclesiological views, finding that their key category for conceiving of church life was sobornost. The author also focuses on the peculiarities of the Society’s legal status and its actual position within the contexts of life within the church and under Soviet legislation in the early 1920s. Here, for the first time, the question of the organization’s relationship with the Petrograd Diocesan Council is posed, and analysis leads us to conclude that there was a conflict between the agencies of diocesan administration and the social movement within the church, which was clearly manifest in the late 1910s and early 1920s. The Society’s potential was realized after the liquidation of the Diocesan Council, when as a group free from the reins of the diocesan administration system, it turned out to be the largest and most representative church association in Petrograd, striving to influence a whole range of issues related to parish life. The article also attempts to outline the connection between the Society and preceding and subsequent phenomena within post-revolutionary church life, including the Local Council of 1917–1918 and the Renovationist movement, whose participants were directly related to the Society.